1996
DOI: 10.1101/gr.6.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Cross-screening: a new method to assemble clones rapidly and unambiguously into contigs.

Abstract: We have developed a new procedure that relies on an array of cross-hybridization tests to order a set of random clones into a contig. The method, called cross-screening, uses each clone as a target and its end sequences as probes, in a matrix of reciprocal cross-hybridization tests performed on a single blot. The relationships among the clones are determined rapidly from the pairwise tests, allowing clone order to be determined directly. We have applied this technique to DNAs from a set of overlapping ~ clones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The cytological positions of the transgene inserts were determined with polytene chromosomes isolated from late third instar larvae (24) hybridized with the P element construct as a probe (10). Map positions were established at higher resolution by hybridization of cloned fragments of adjacent genomic DNA to cosmid and bacterial artificial chromosome (BAC) clones from the fourth chromosome (20,45). The DNA flanking the P element inserts was cloned in vector pCR3.1 (Invitrogen) by using inverse PCR (14).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The cytological positions of the transgene inserts were determined with polytene chromosomes isolated from late third instar larvae (24) hybridized with the P element construct as a probe (10). Map positions were established at higher resolution by hybridization of cloned fragments of adjacent genomic DNA to cosmid and bacterial artificial chromosome (BAC) clones from the fourth chromosome (20,45). The DNA flanking the P element inserts was cloned in vector pCR3.1 (Invitrogen) by using inverse PCR (14).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic analysis indicated that line 2-M1021R is an allele of ci; homozygotes have a fusion of wing veins 4 and 5 because of inappropriate expression of ci (R. Holmgren, personal communication). Sequencing of the tag clone places the insertion site within a cluster of repeats upstream of the ci transcript (20). This 3-kilobase region has a similar, nonidentical, AT-rich sequence present approximately every 200 bp.…”
Section: Recovery Of Transgenic Lines On the Fourth Chromosomementioning
confidence: 99%
See 3 more Smart Citations